Creativity: a personal view - A. O. Moscardini, (Ukrainian Cultural Studies, 2020)
The meaning of creativity is an illusive concept and highly subjective. This article focusses on four strands (curiosity, illusion, execution and innovation) and weaves them into a tapestry that represents the personal view of the author. An innovative hypothesis is that creativity is related to the bicameral mind and this is backed by reference to current neuroscientific research. The author is by profession a mathematician but posits in the article that at the micro level there is no difference between Art and Science regarding the act of creation. The article discusses this process from four different angles; curiosity, illusion, execution and innovation. The final synthesis is left to the reader.
Keywords: Bicameral Brain, Constructivist theory of the brain, Creativity, illusion, innovation